Manufacturing method of X-ray absorption grating

Through bonding and lithography technology between high-doped silicon wafers and intrinsic silicon wafers, a silicon-based grating structure with conductive sidewall insulation is formed, and metal filling is directly performed, which solves the sealing phenomenon and process complexity problems and improves the X-ray Absorbing grating quality and production efficiency.

CN119270404APending Publication Date: 2025-01-07SHENZHEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411392463.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

There is a sealing phenomenon in the existing X-ray absorption grating manufacturing process, which leads to insufficient metallization filling and affects the quality of the absorption grating. The existing methods have complex processes, high costs, poor stability, and low yield.

Method used

High-doped silicon wafers are bonded to intrinsic silicon wafers to form a silicon-based grating micro-period trench structure with conductive bottom and sidewall insulation. The preset period structure is formed by spin-coating photoresist and etching, and metal is directly carried out. Filling avoids the use of insulating film and special electroplating solution.

Benefits of technology

The process flow is simplified, the metallization filling effect and grating performance are improved, the production cost and manufacturing difficulty are reduced, and the mass production efficiency and yield rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119270404A_ABST
    Figure CN119270404A_ABST
Patent Text Reader

Abstract

The invention discloses a method for manufacturing an X-ray absorption grating, which belongs to the technical field of X-ray imaging and application, and comprises the following steps of: carrying out semiconductor bonding connection on a doped monocrystalline silicon wafer (high conductivity) and an intrinsic monocrystalline silicon wafer (weak conductivity) to synthesize a double-layer silicon wafer with relatively large interlayer conductivity difference; then, a periodic micro groove preset by the grating is manufactured on the weak-conductivity intrinsic monocrystalline silicon layer through a semiconductor thinning-photoetching-etching process, the bottom of the groove reaches the strong-conductivity doped monocrystalline silicon layer, and therefore the silicon grating with the conductive bottom and the insulated side wall is constructed; and finally, metallization filling is carried out through electroplating, and manufacturing of the X-ray absorption grating is achieved. The technical scheme of the invention is based on a current relatively mature semiconductor manufacturing process, has relatively high technical maturity and reliability, is relatively simple in process and relatively low in batch manufacturing cost, can effectively solve the problems of sealing and the like of electroplating filling, and greatly improves the manufacturing efficiency and the yield of the grating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of X-ray imaging and application technology, and more particularly to a method for manufacturing an X-ray absorption grating. Background Art

[0002] X-ray phase contrast imaging can simultaneously obtain the X-ray absorption, phase contrast and dark field images of the sample. Compared with traditional X-ray absorption imaging technology, it shows great application potential in the fields of biological soft tissue imaging, non-destructive testing of organic materials or devices. The X-ray absorption grating is the core component of the phase contrast imaging system. As a source grating, it can increase the coherence of X-rays. As an analysis grating, it can be used to form moiré fringes, which is convenient for extracting phase information. The quality of the absorption grating is directly related to the quality of the phase contrast imaging system, but its production still faces many challenges. Structurally, the period of the X-ray absorption grating is several microns. In order to absorb as many X-rays as possible, its depth needs to be large, which requires it to have a high aspect ratio. In such a structure, metallization filling is performed, and the current mainstream filling method is to use gold electroplating process. However, the sealing phenomenon is easy to occur during the electroplating process of the high aspect ratio structure, which leads to cavities in the filling metal, seriously affecting the quality of the X-ray absorption grating.

[0003] In response to the above problems, researchers have tried to develop several solutions to suppress the sealing phenomenon. In the prior art, there is a method of using coating technology to prepare an insulating film on the silicon sidewall, thereby suppressing the metal growth on the sidewall during electroplating, so that the metal grows from the bottom of the micro-groove upward until the groove is filled. A new electroplating solution formula containing bismuth ions has also been proposed. Bismuth ions can suppress the growth of high potential on the sidewall, thereby achieving conformal deposition and finally filling the silicon micro-grooves.

[0004] Although the existing technology has improved the manufacturing level of X-ray absorption gratings to a certain extent, these methods all have some limitations to varying degrees. The coating technology method requires the coating of an insulating film on the sidewalls of silicon micro-grooves, but the coating of the sidewalls of high aspect ratio silicon grooves is itself a technical problem. Not only is the process complicated, but it will also introduce new process problems, which will greatly increase the difficulty and cost of manufacturing, and the yield and stability are also difficult to guarantee. The new plating solution formula containing bismuth ions suppresses the metal growth on the sidewalls of the micro-grooves by regulating the composition of the plating solution. This method requires precise control of the ion concentration and plating parameters of the plating solution. On the one hand, it will limit the speed of electroplating and reduce processing efficiency; on the other hand, it will also lead to problems such as poor stability and low fault tolerance, limiting the yield. Summary of the invention

[0005] In view of this, the present invention proposes a novel X-ray absorption grating manufacturing method to overcome the technical bottleneck of existing X-ray absorption grating manufacturing, improve the micro-groove metallization filling effect, reduce the manufacturing process difficulty and production cost, and effectively improve production efficiency and yield rate.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for manufacturing an X-ray absorption grating comprises the following steps:

[0008] S1. Select appropriate high-doped silicon wafers and intrinsic silicon wafers according to the target grating structure size, polish the bonding surfaces of the high-doped silicon wafers and intrinsic silicon wafers, clean them, and then dry them naturally for use;

[0009] S2. Using the highly doped silicon wafer processed in step S1 as the substrate layer and the intrinsic silicon wafer as the surface layer, aligning the polished surfaces of the two wafers and performing wafer bonding, followed by annealing;

[0010] S3. Thinning the surface layer after bonding in step S2 to the depth of the grating groove and removing the surface oxide film;

[0011] S4. Spin-coating a photoresist on the surface layer after the treatment in step S3, and then photolithography a preset grating period structure template, and then etching the surface layer under the template shielding until the substrate layer is exposed, and removing the photoresist to obtain a silicon grating of a preset period and depth;

[0012] S5. Clean the grating obtained in step S4, and then fill the grating grooves with metal to obtain an X-ray absorption grating.

[0013] Preferably, the highly doped silicon wafer in step S1 is N-type silicon doped with phosphorus or arsenic or P-type silicon doped with boron or gallium.

[0014] Preferably, the polishing in step S1 adopts single-wafer CMP chemical mechanical polishing, and the surface micro-roughness after polishing is controlled to be less than 10 nm.

[0015] Preferably, the bonding in step S2 adopts one or more of Si-Si bonding, SiO2-SiO2 bonding, gold-gold bonding, and polymer bonding.

[0016] Preferably, in step S3, 5 volume % hydrofluoric acid is used for immersion for 30 seconds to remove the oxide film.

[0017] Preferably, the specific operation of removing the photoresist in step S4 is:

[0018] Depending on the type and composition of the photoresist, the silicon wafer is immersed in a dedicated photoresist organic solvent for 5-10 minutes, and then rinsed with deionized water to remove the residual organic solvent.

[0019] Preferably, in step S5, alcohol immersion and ultrasonic cleaning are performed for 10-15 minutes.

[0020] Preferably, in step S5, metal filling is performed by electroplating, electrophoresis or chemical plating.

[0021] Preferably, the metal in step S5 is one of gold, tungsten, platinum, lead and nickel.

[0022] It can be seen from the above technical solutions that, compared with the prior art, the present invention discloses a method for manufacturing an X-ray absorption grating, which has the following beneficial effects:

[0023] The present invention adopts mature semiconductor manufacturing technology to construct a silicon-based grating micro-periodic groove structure with bottom conductive and sidewall insulating, without the need for insulating film plating and the need for controlling the use of special electroplating liquid. The process is relatively simple, highly controllable, and stable, and the efficiency of mass production is high, the yield rate is high, and the cost is relatively low.

[0024] The silicon-based grating micro-groove structure constructed by the technical solution of the present invention can effectively solve the electroplating sealing problem, making the metallization filling effect better and the grating performance more reliable;

[0025] The technical solution of the present invention has high process flexibility, and suitable grating materials, filling materials and bonding forms can be selected according to application requirements;

[0026] The technical solution of the present invention can control the depth of the grating period micro-grooves by the thickness of the weak conductive layer, so that the etching process is simpler and has a high fault tolerance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0028] Figure 1 is a structural diagram after bonding of Example 1;

[0029] Figure 2 This is a structural diagram related to the grating periodic structure template of Example 1;

[0030] Figure 3 This is a structural diagram of the grating after etching of Example 1;

[0031] Figure 4 It is a schematic diagram related to metal filling in Example 1;

[0032] Figure 5This is a finished product structure diagram of Example 1;

[0033] Figure 6 The bonding structure of Example 2

[0034] In the figure, 1-substrate layer, 2-surface layer, 3-photoresist, 4-cathode, 5-platinum electrode, 6-electroplating solution, 7-magnetic stirring bar, 8-gold, and 9-copper layer. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] The grating groove depth is 50μm, the processing cycle is 5μm, and the specific preparation steps are as follows:

[0038] S1. Considering the margin required for processing, the surface layer silicon wafer is 4-inch intrinsic single crystal silicon, 0.1mm thick, and its resistivity is greater than 10000Ω·cm. The substrate layer silicon wafer is 4-inch N-type silicon, 0.6mm thick, and the resistivity is 1-30Ω·cm. Two 4-inch silicon wafers are selected. In order to improve the efficiency of subsequent processing, the device layer silicon wafer needs to be roughly thinned to 0.1mm. After thinning, the flatness error needs to be less than 5μm, and the upper and lower parallelism errors need to be less than 5μm. The bonding surfaces of the two are polished by single-chip CMP chemical mechanical polishing, and the surface micro-roughness after polishing is controlled to be less than 10nm. After the surface is polished, it is cleaned and dried naturally for use;

[0039] S2. The highly doped silicon wafer processed in step S1 is used as the substrate layer, and the intrinsic silicon wafer is used as the surface layer. The polished surfaces of the two are aligned in the bonding machine. The alignment error needs to be controlled to be less than 3μm. After aligning the silicon wafer, silicon-silicon bonding is performed at a temperature of 200-250℃ and a pressure of 30MPa. After bonding, annealing is performed at 300℃ for 8h. Figure 1 As shown;

[0040] S3. After bonding, the surface of the silicon wafer is trimmed with a scraper, and then the surface layer is thinned to 50μm in a thinning machine. The flatness error needs to be controlled to be less than 5μm, and the upper and lower parallelism error needs to be less than 3μm. Then, low-concentration (5%) hydrofluoric acid is used to soak for about 30s to remove the surface oxide film, and the thinned surface is polished. The surface roughness must be less than 0.1μm for subsequent deep etching;

[0041] S4. Spin-coat the surface layer treated in step S3 with photoresist, and then photolithograph a preset grating periodic structure template, such as Figure 2 As shown, the surface layer is then etched about 50 μm under the template shielding until the surface layer is exposed, as shown in FIG. Figure 3 As shown, the photoresist is removed to obtain a silicon grating with a period of 5 μm and a depth of about 50 μm. After laser cutting and block cutting, the grating cross-section shaping degree is checked under an electron microscope;

[0042] S5. Soak the grating in alcohol and ultrasonically clean it for about 10 minutes to remove oil and impurities on the surface of the silicon grating. Pre-plate copper for 2 minutes on the bottom and back of the grating to obtain a continuous conductive layer, such as Figure 4 As shown, the back of the N-type single crystal silicon is shielded for electroplating gold (current density 2-5mA / cm 2 , temperature condition 55℃) fills the grating grooves from bottom to top to obtain a complete X-ray grating, such as Figure 5 shown.

[0043] Example 2

[0044] The grating groove depth is 60μm, the processing cycle is 6μm, and the specific preparation steps are as follows:

[0045] S1. Considering the margin required for processing and the bonding process requirements, the surface layer silicon wafer is 6-inch intrinsic single crystal silicon, 0.3mm thick, and its resistivity is greater than 10000Ω·cm. The substrate layer silicon wafer is 6-inch N-type silicon, 0.6mm thick, and the resistivity is 1-30Ω·cm. The bonding surfaces of the two are polished by single-chip CMP chemical mechanical polishing, and the surface micro-roughness after polishing is controlled to be less than 10nm. After the surface is polished, it is cleaned and dried naturally for standby use;

[0046] S2. The highly doped silicon wafer processed in step S1 is used as the substrate layer, and the intrinsic silicon wafer is used as the surface layer. After alignment in the bonding machine, the N-type silicon wafer of the substrate layer is bonded to the 0.1 mm thick copper sheet by silicon-gold bonding under corresponding conditions. The bonding temperature is 350-380°C, and the loading pressure is 1×10 4 Pa, keep at 650℃ for 45min after bonding, cool naturally, then thin the copper layer to less than 10μm, polish the copper layer surface, control its surface roughness to more than 2nm according to the subsequent silicon-gold bonding process, align the treated copper layer with the polished surface of the surface silicon wafer for silicon-gold bonding, the bonding temperature is 350-380℃, the loading pressure is 1×10 4 Pa, then annealed at 550-600 °C for 8 h;

[0047] S3. After bonding is completed, the surface layer thickness is roughly ground to about 100μm, and the surface of the silicon wafer is trimmed with a scraper. Then, the silicon wafer device layer is thinned to 60μm on a thinning machine. The flatness error needs to be controlled to be less than 5μm, and the upper and lower parallelism error needs to be less than 5μm. Figure 6As shown; then soak in low concentration (5%) hydrofluoric acid for about 30 seconds to remove the surface oxide film, polish the thinned surface, and the surface roughness must be less than 0.1μm to prepare for subsequent deep etching;

[0048] S4. Spin-coat the surface layer treated in step S3 with photoresist, then photolithograph a preset grating periodic structure template, and then use deep silicon etching to etch down the intrinsic silicon layer with the mask template under the template shielding until the middle copper layer is exposed, the groove inclination is vertical, the length direction straightness is less than 5μm, and the cross-sectional size error is ±1μm. Remove the photoresist to obtain a silicon grating with a period of 6μm and a depth of about 60μm. After laser cutting and dividing, check the grating cross-sectional molding degree under an electron microscope;

[0049] S5. Soak the grating in alcohol and ultrasonically clean it for about 10 minutes to remove oil and impurities on the silicon grating surface, and shield the back of the N-type single crystal silicon for electroplating gold (current density 2-5mA / cm 2 , temperature condition 55℃) to fill the grating grooves from bottom to top to obtain a complete X-ray grating.

[0050] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0051] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for manufacturing an X-ray absorption grating, characterized in that: The following steps are involved: S1. Select appropriate high-doped silicon wafers and intrinsic silicon wafers according to the target grating structure size, polish the bonding surfaces of the high-doped silicon wafers and intrinsic silicon wafers, clean them, and then dry them naturally for use; S2. Using the highly doped silicon wafer processed in step S1 as the substrate layer and the intrinsic silicon wafer as the surface layer, aligning the polished surfaces of the two wafers and performing wafer bonding, followed by annealing; S3. Thinning the surface layer after bonding in step S2 to the depth of the grating groove and removing the surface oxide film; S4. Spin-coating a photoresist on the surface layer after the treatment in step S3, and then photolithography a preset grating period structure template, and then etching the surface layer under the template shielding until the substrate layer is exposed, and removing the photoresist to obtain a silicon grating of a preset period and depth; S5. Clean the grating obtained in step S4, and then fill the grating grooves with metal to obtain an X-ray absorption grating.

2. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: The highly doped silicon wafer in step S1 is N-type silicon doped with phosphorus or arsenic or P-type silicon doped with boron or gallium.

3. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: The polishing in step S1 adopts single-wafer CMP chemical mechanical polishing, and the surface micro-roughness after polishing is controlled to be less than 10nm.

4. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: The bonding in step S2 adopts one or more of Si-Si bonding, SiO2-SiO2 bonding, gold-gold bonding, and polymer bonding.

5. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: In step S3, 5% by volume hydrofluoric acid is used for immersion for 30 seconds to remove the oxide film.

6. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: The specific operation of removing the photoresist in step S4 is: Depending on the composition and type of the photoresist, the silicon wafer is immersed in a dedicated organic solvent for 5-10 minutes, and then rinsed with deionized water to remove the residual organic solvent.

7. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: In step S5, alcohol immersion and ultrasonic cleaning are performed for 10-15 minutes.

8. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: In step S5, metal filling is performed by electroplating, electrophoresis or chemical plating.

9. The method for manufacturing an X-ray absorption grating according to claim 1, characterized in that: The metal in step S5 is one of gold, tungsten, platinum, lead and nickel.

Citation Information

Patent Citations

  • Grid for radiation imaging and method for producing the same

    CN102741709A

  • Manufacturing method for metallic lattice, and metallic lattice

    WO2012008118A1